Could FXIII Deficiency Influence Intracerebral Hemorrhage after Neurosurgery? - Jordan , Estela Val (Current Practice in Medical Science Vol. 8, 2022)
The primary goal was to assess the impact of perioperative FXIII levels on ICH after brain surgery. A prospective, 18-month observational study was carried out at a third-level hospital in Spain. It included all consecutive adults (18 years of age or older) who underwent elective brain tumour surgery and stayed in the Neurointensive Care Unit afterward (N-ICU). Younger than 18 years of age, informed refusal, death in the OR, incomplete blood sample or non-tumoral tissue were exclusion criteria.Three blood samples evaluated FXIII levels (A-presurgical, B-postsurgical and C-24 hours after surgery). There were 109 patients in the study. In 39 of them, ICH was finally confirmed (35,78 percent). Inferential analyses revealed a statistical link between ICU stay length (p0,01) and male gender (p0,03) and ICH. The average of FXIII was lower in ICH patients, particularly in the B sample (A 71,2 percent, B 51,57 percent, C 52,14 percent). Acquired FXIIID (70%) after brain tumour surgery increased ICH, suggesting that it could be used as a risk marker for haemorrhage. ICH was also linked to baseline variation, male gender, and a longer stay in the ICU. Normal coagulation tests did not rule out FXIII disorder. FXIIID detection and replacement therapy could become a therapeutic target in future studies.brain tumor